(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Colorectal cancer (CRC) is the second most lethal cancer in the world. Due to late discovery, a high recurrence rate, and multi-drug resistance, CRC care is difficult. Herbs and spices used in cooking have been demonstrated to include CRC protective effectors and can even be utilised as an anti-CRC adjuvant treatment when taken in large dosages. Herbs and spices include several bioactive chemicals that have numerous health benefits. These herbs and spices’ chemopreventive activities are primarily mediated by multiple routes, including caspase activation, the extrinsic apoptotic pathway, and the modulation of ER-stress-induced apoptosis. As a result, Ginger (Zingiber officinale) was chosen for this study and studied for its chemoprotective or chemotherapeutic effects in CRC treatment, as well as the underlying molecular mechanisms of action. This study first reviewed the molecular base of CRC formation, followed by culinary and traditional usage, current scientific research, and publications of chosen spices and plants.